2019
DOI: 10.1051/matecconf/201926602011
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework to determine Medical Equipment Maintenance in Hospital Using RCM Method

Abstract: Maintenance services are performed to ensure the equipment is operating according to manufacturer standard and maintained at a desired level of quality. The implementation of maintenance services may prevent unexpected breakdown and disruption of operations in a hospital. However, there were numbers of cases reported on the frequent breakdown of medical equipment even though the maintenance program is in place and practised. Therefore, the reliability of the maintenance services was questioned especially when … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 12 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…The output of this system was divided into three priority levels, and the quantities of medical equipment at each level are tabulated in Table 6 . The clustering analysis of the replacement programme demonstrated that the low priority medical equipment consists of active units with the majority of 96% below ten ( 10 ) years as tabulated in Table 9 . The manufacturer still provided the support service, and the service provider required only one time of PPM frequency, while the routine inspection was annually conducted.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The output of this system was divided into three priority levels, and the quantities of medical equipment at each level are tabulated in Table 6 . The clustering analysis of the replacement programme demonstrated that the low priority medical equipment consists of active units with the majority of 96% below ten ( 10 ) years as tabulated in Table 9 . The manufacturer still provided the support service, and the service provider required only one time of PPM frequency, while the routine inspection was annually conducted.…”
Section: Resultsmentioning
confidence: 99%
“…The combination of 16 novel features, which are ( 1 ) age, ( 2 ) function, ( 3 ) PM status, ( 4 ) missed PPM, ( 5 ) maintenance requirement, ( 6 ) maintenance complexity, ( 7 ) downtime, ( 8 ) operations, ( 9 ) number of failures, ( 10 ) response time, ( 11 ) repair time, ( 12 ) backup and alternative unit, ( 13 ) maintenance cost, ( 14 ) asset status, ( 15 ) obsolescence, and ( 16 ) asset condition was used for prioritisation assessment and prediction of medical equipment's comprehensive strategic maintenance management. The system development measured 13,352 various types of medical equipment used in Malaysian public health clinic facilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Maintenance management of medical equipment is crucial to ensure that a machine operates in accordance with manufacturer specifications and guarantees the patients and users safety (10). Failure of medical equipment may affect the healthcare services effectiveness and cause severe injury to the patients and harm the environment (11).…”
Section: Introductionmentioning
confidence: 99%